From the Guadalupan Symbol: Criteria for the Pastoral Moment (Teología, 2015)
The author of this collaboration reflects on the possibility of being protagonists in the shared construction of a more fraternal and authentically plural present. The guadalupan symbol offers a model which can help to take the opportunity of this pastoral moment in the theology. The guadalupan event continues to take place and in an analogical way opens for us and proposes a set of fecund precisions, suggestions and questions. As a symbol, the image of Our Lady of Guadalupe is its nuclear element, which shapes and promotes the incarnation of an evangelizing praxis. A dynamic of dialogue and inculturation, which fosters the courage to adopt an attitude of openness to the Saving Love, and to share this Love as People, with cordiality and mercy, living place for the others, and for cultural fusion.